Auditoría de Gestión al Gobierno Autónomo Descentralizado Parroquial de San Antonio de las Aradas, cantón Quilanga, provincia de Loja, período 2021 - Ojeda Calva, Letty Abigail (2024)
The following work focuses on the performance audit of the Autonomous Decentralized Parish Government of San Antonio de las Aradas, Quilanga canton, Loja province for the year 2021. Among the main objectives of this audit were to conduct a diagnosis of the parish government to identify deficiencies and to conduct a SWOT analysis, to examine the internal control system to identify risks, to verify compliance with laws and regulations, to evaluate staff performance utilizing management indicators, and to prepare an audit report with conclusions and recommendations. The objective of this study was to use a mixed approach combining qualitative and quantitative data, and a non-experimental design in order to collect and analyze data without altering the conditions of the environment, which resulted in results which revealed a variety of deficiencies. An ineffective risk mitigation plan and a lack of a functional manual were identified as issues in internal control. Furthermore, it was found that no significant tools or procedures were developed for the institution's activities. There was also a lack of management indicators, which made it difficult to evaluate staff performance and achieve institutional goals. It was also discovered that most of the staff did not have professional degrees, and that the Development and Land Management Plan had not been renewed, which affected the planning and execution of projects. Due to an inadequate estimation of resources, the budget was overestimated by 1.14%, causing a debt for the following year. At the conclusion of the management audit, the findings were established in the final report, along with their respective conclusions and recommendations to the officials of the GAD Parroquial so that they can put them into practice and improve their management, complying efficiently and effectively with their obligations and proposed objectives. The purpose of this study is to demonstrate the importance of management auditing in optimizing the administrative processes of parish governments and to suggest corrective measures that may contribute to institutional strengthening and achieve the objectives proposed.